Rencana Survei Pemetaan Jaringan Perpipaan Sistem Penyediaan Air Minum (SPAM) IKK Ketahun Kabupaten Bengkulu Utara - Muhamad Rifky Kusdinar; Rezi Munizar; Buyung Mantap (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Safe and sustainable drinking water services require distribution network planning supported by accurate spatial data. This study aimed to develop a pipeline network survey and mapping plan for the Subdistrict Capital Water Supply System (SPAM IKK) in Ketahun, North Bengkulu Regency, as the basis for preparing a Detail Engineering Design (DED). A quantitative descriptive approach with field surveys was employed by collecting topographic, land-use, road network, utility, settlement, and elevation data using GPS, GIS, and EPANET hydraulic modeling. The results indicate that pipeline routes following existing road corridors provide greater construction and operational efficiency. Projected water demand reached approximately 40 L/s at the end of the planning period, while hydraulic simulation confirmed that pressure and flow velocity satisfied technical standards for water supply systems. The integration of field surveys, digital mapping, and hydraulic simulation provides an accurate and effective basis for sustainable drinking water distribution planning.